2011
DOI: 10.1371/journal.pone.0027853
|View full text |Cite|
|
Sign up to set email alerts
|

Cadmium-Induced Oxidative Stress and Apoptotic Changes in the Testis of Freshwater Crab, Sinopotamon henanense

Abstract: Cadmium (Cd), one of the most toxic environmental and industrial pollutants, is known to exert gonadotoxic and spermiotoxic effects. In the present study, we examined the toxic effect of Cd on the testis of freshwater crab, Sinopotamon henanense. Crabs were exposed to different Cd concentrations (from 0 to 116.00 mg·L−1) for 7 d. Oxidative stress and apoptotic changes in the testes were detected. The activities of SOD, GPx and CAT initially increased and subsequently decreased with increasing Cd concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 58 publications
(63 reference statements)
3
46
1
Order By: Relevance
“…The activation of GST enzymes triggered by cadmium exposure was also observed in several marine worms (Won et al, 2011 and references herein). Moreover, according to previous studies GST may have a protective role against Cd toxicity, in terms of physiological alterations related to metabolism and cell protection (Wang and Wang, 2009;Wang et al, 2011;Won et al, 2011). Overall, the results from the present work suggest that animals from Minho and Lima estuaries use different detoxifying mechanisms to deal with cadmium exposure, and support the role of glutathione as chelating agent, conferring enhanced tolerance to this metal.…”
Section: Discussionsupporting
confidence: 84%
“…The activation of GST enzymes triggered by cadmium exposure was also observed in several marine worms (Won et al, 2011 and references herein). Moreover, according to previous studies GST may have a protective role against Cd toxicity, in terms of physiological alterations related to metabolism and cell protection (Wang and Wang, 2009;Wang et al, 2011;Won et al, 2011). Overall, the results from the present work suggest that animals from Minho and Lima estuaries use different detoxifying mechanisms to deal with cadmium exposure, and support the role of glutathione as chelating agent, conferring enhanced tolerance to this metal.…”
Section: Discussionsupporting
confidence: 84%
“…Cadmium induces reproductive damage mainly via oxidative stress [32,33,34,35]. Usual parameters such as GSH, SOD, and MDA were used as indices to measure antioxidative stress-induced damage in cells and organs.…”
Section: Discussionmentioning
confidence: 99%
“…ROS could cause oxidative stress by reacting with macromolecules and lead to damages, such as apoptosis and membrane lipid peroxidation [7,48]. Studies from our laboratory also found alterations in the levels of malondialdehyde (MDA) which is the final decomposition product of lipid peroxidation caused by ROS, and the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) after Cd exposure [8,40,49,50]. In the defense against Cd-stress, one of the metal-binding proteins is metallothionein (MT), a small protein with a significant concentration of cysteine.…”
Section: Discussionmentioning
confidence: 99%